Teaching IELTS Speaking Skills: How Is the Students"™ Preparation For Taking the Test? - Fitria, Tira Nur (Journal of English Education Program, 2024)
This research describes teaching IELTS Speaking Speaking and students"™ preparation for taking the IELTS Speaking. This research is library research. The analysis shows that The IELTS Speaking test consists of three parts: Introduction, Cue Card, and Follow-up Questions. The Introduction section introduces the interviewer and asks simple questions related to everyday life to help participants feel comfortable. The Cue Card section allows participants to prepare answers on a predetermined topic, usually related to personal experiences or specific situations. The Follow-up Questions section tests participants' ability to organize and convey ideas in a clear and structured manner. The IELTS Speaking construct is characterized by four areas: Fluency and Coherence, Lexical Resource, Grammar Range and Accuracy, and Pronunciation. Preparation for the test involves regular practice, understanding basic grammar, paying attention to intonation and pronunciation, and avoiding mistakes. To prepare, organize the schedule, ensure optimal physical and mental conditions, get enough sleep, and bring necessary documents and equipment. Developing English-speaking skills and honing communication skills can help students achieve a good score on the IELTS Speaking test and improve their overall English-speaking skills. To produce quality students with good IELTS skills, students should be familiar with IELTS and have experience completing IELTS simulation tests. By preparing well and practicing regularly, students can improve their English proficiency and score higher on the IELTS Speaking test.